Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai Negeri Sipil Di Sekretariat Daerah Kabupaten Kepulauan Sula - Umamit, Sulma; Mandey, Jantje; Rares, Joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : The research was conducted on the basis of initial observations that civilservants in performing basic tasks and functions indicated less comply with the applicable rules,especially rules regarding discipline in performing the task. Thus, the study aims to "know theeffect of the application of disciplinary oversight of the civil servants working in the RegionalSecretariat Sula Islands".The method used in this research is descriptive method with quantitative approach. Purposivesample of respondents assigned as many as 69 people, and a questionnaire distributed data collectiontechniques for obtaining primary data, while the secondary data obtained through technicaldocumentation. All data and information obtained through surveys and direct observation techniques.Once the data is collected, analyzed using analytical techniques percentage (frequency table), followedby product moment correlation analysis and simple linear regression.The results showed that: Implementation of the functions of supervision and discipline ofemployees working in the Secretariat of the Sula Islands area identified in the category "medium", butoversight tends to be high, while labor discipline of employees tends to be low. Supervision positive andsignificant impact on employee discipline, particularly at the district secretariat Sula Islands. Thefunctional relationship between the two variables linear patterned positive and contributive.Thus, it can be concluded that the proposed research hypotheses can be tested empiricallyenforceability as well as to justify the underlying theories. Direct supervisor needs to streamline thesupervision attached to subordinates in order to improve their work discipline; There needs to becontinuous socialization discipline rules as well take an act decisively to employees who deviate fromthese rules.Key words:Monitoring Functions, Discipline employee